Photonic Dirac waveguide in inhomogeneous spoof surface plasmonic metasurfaces - Yang Yuting; Zhang Juyi; Yang Bin; Liu Shiyu; Zhang Wenjie; Shen Xiaopeng; Shi Liwei; Hang Zhi Hong (Nanophotonics, 2024)
The metamaterial with artificial synthetic gauge field has been proved as an excellent platform to manipulate the transport of the electromagnetic wave. Here we propose an inhomogeneous spoof surface plasmonic metasurface to construct an in-plane pseudo-magnetic field, which is generated by engineering the gradient variation of the opened Dirac cone corresponding to spatially varying mass term. The chiral zeroth-order Landau level is induced by the strong pseudo-magnetic field. Based on the bulk state propagation of the chiral Landau level, the photonic Dirac waveguide is designed and demonstrated in the experimental measurement, in which the unidirectionally guided electromagnetic mode supports the high-capacity of energy transport. Without breaking the time-reversal symmetry, our proposal structure paves a new way for realizing the artificial in-plane magnetic field and photonic Dirac waveguide in metamaterial, and have potential for designing integrated photonic devices in practical applications.